(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
This study evaluates sustainable development strategies in East Nusa Tenggara (NTT) by analyzing the roles of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), population size, and literacy rate in improving community welfare. Secondary data from 2013 to 2023, covering 22 regencies/cities in NTT, were used in this research. Panel data analysis with a Fixed Effect Model (FEM) was selected based on Chow and Hausman tests. The results indicate that GRDP has a positive but insignificant effect on poverty levels, whereas HDI and literacy rate have significant negative effects. Population size shows a positive but insignificant effect. The adjusted R-squared value of 99.4% indicates that the independent variables collectively contribute substantially to variations in poverty levels. This study emphasizes the importance of improving quality of life through education and healthcare as effective strategies to reduce poverty in NTT. The findings provide policy recommendations to integrate economic growth with human resource development to achieve inclusive and sustainable development.